Differential Scanning Calorimetric Analysis of Drug-Polymer Interaction in Glutinous Rice Based Microbeads - K. Sachan, Nikhil; Ghosh, S.K.; Bhattacharya, A. (Asian Journal of Chemistry, 2012)
Controlled drug delivery occurs when a polymer, whether natural or synthetic, is judiciously combined with a drug or other active agent in such a way that the active agent is released from the material in a predetermined manner. The differential scanning calorimetry (DSC) offers a rapid convenient and conclusive methodology during preformulation testing, to confirm about the drug-polymer compatibility. It allows and enhances probability of any drug-polymer incompatibility to be established and identified instantaneously. The Assam Bora rice, a variety of glutinous rice cultivated mainly in Assam region was taken as polymer backbone along with sodium alginate in formulation. The fabricated drug delivery systems, formulated so as to provide controlled release of drug were subjected to DSC analysis and a comparative interpretation done by matching the thermograms recorded for drug, polymers and their blend. The results revealed that the matrix micro devices have sufficient stability and there is no indication of chemical interaction between drug and polymer backbone.